Partnerstwo w relacji małżeńskiej jako współczesna wartość wychowania - Joanna Ostrouch-Kamińska (Problemy Wczesnej Edukacji)
Today we observe the dynamic changes in relations between the sexes in the family, which appear as a result of economic, cultural, and social transformation, the growth of women’s economic strength, as well as the level of their education, and the development of the ideas of the equal rights of women and men in the labour market and in social life. Hitherto existing research results show that Poles are increasingly in favour of the egalitarian family model and declare their wish to build their relationships based on equality.